Ab Initio Metadynamics Simulations of Hexafluoroisopropanol Solvent Effects: Synergistic Role of Solvent H‐Bonding Networks and Solvent‐Solute C−H/π Interactions. Issue 17 (16th February 2023) - Hu, Xinmin; Zhao, Xia; Lv, Xiangying; Wu, Yan‐Bo; Bu, Yuxiang; Lu, Gang
Abstract: The solvent effects in Friedel–Crafts cycloalkylation of epoxides and Cope rearrangement of aldimines were investigated by using ab initio molecular dynamics simulations. Explicit molecular treatments were applied for both reactants and solvents. The reaction mechanisms were elucidated via free energy calculations based on metadynamics simulations. The results reveal that both reactions proceed in a concerted fashion. Key solvent‐substrate interactions are identified from the structures of transition states with explicit solvent molecules. The remarkable promotion effect of hexafluoroisopropanol solvent is ascribed to the synergistic effect of H‐bonding networks and C−H/π interactions with substrates. Abstract : Ab initio metadynamics simulations under explicit solvent environments were performed to investigate the promotion effect of HFIP solvent in Friedel–Crafts alkylation and Cope rearrangement reactions. The H‐bonding network and the HFIP‐substrate C−H/π interaction are identified as the major factors affecting reactivity.